(untitled) (Journal of Academic Research, 2021)
this paper presents a new approach to hide sensitive data inside grayscale digital image. It makes use of combining the RSA encryption algorithm with steganography technique. This approach based on searching for identical bits - two by two bits - between the sensitive data bits and image pixel bits values. In case the bits are non-identical, it hides the sensitive data bits at tow least scientific bits (LSB technique). Two types of images are used for implementing the steganography technique, one is light grayscale image and the other is dark grayscale image. The results of the grayscale are compared with resultant of RGB digital images. The results reveal that MSE, PSNR and correlation coefficient values were satisfactory.